Bridging the Gap: A Short Review of BSCF Composite Materials for Intermediate Temperature SOFC - Abdul Rahman, Nurul Farhana; Abd.Rahman, Hamimah; Tan Kang Huai (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Barium Strontium Cobalt Ferrite (BSCF) is highly regarded as the top choice for solid oxide fuel cell (SOFC) cathodes because of its exceptional catalytic activity in oxygen reduction and superior mixed electrical and ionic conductivity. This abstract provides an overview of recent research efforts focused on the synthesis, characterization, and performance evaluation of BSCF composite materials operating at intermediate temperatures. Various synthesis methods, including solid-state reaction, sol-gel and mechanical milling are discussed, along with characterization techniques such as X-ray diffraction (XRD) and scanning electron microscopy (SEM). Issues related to BSCF composites, such as chemical stability and long-term performance, are discussed, along with recommendations for future research to overcome these obstacles and enhance the commercialization of IT-SOFCs using BSCF composite materials.